Localized Aortic Root Dissection with a Superior Mesenteric Artery Aneurysm - Ikeda, Akihiko (Ann Vasc Dis, 2017)
In this study, the case of a 46-year-old female patient with localized aortic root dissection and a superior mesenteric artery (SMA) aneurysm is described. Computed tomographic angiography could not clearly delineate an intimal flap in the aortic root, but it detected SMA aneurysm, which implied the presence of a vulnerability of the aortic wall. Finally, transesophageal echocardiography (TEE) evidently showed the intimal flap localized in the aortic root. The present case suggests that TEE is of paramount importance for detecting localized aortic root dissection. In addition, a coexisting vascular lesion may be a clue to diagnose another vascular lesion.